Application of Three-Tier Test for Identification of Misconception Student Quantity on Magnetic Pole - Reny Silviani; Riski Muliyani; Yudi Kurniawan (International Journal of Multi Discipline Science, 2020)
This study aimed to identify the quantity of students who have misconceptions about magnetic poles. This research was a descriptive quantitative study with purposive sampling as the sampling technique. The instrument used was a three-tier test, which is to identify the quantity of students with misconceptions. The results of the study showed that there is the highest misconception that a larger magnetic attraction is stronger than a small magnet. It is hoped that the results of this study can be used as a reference for further research and find solutions to these misconceptions.